Phenomenal self and dream self - Kara, Hayrettin; Selvi, Yavuz (Küre İletişim Grubu A.Ş., 2017)
The concept of self is a complicated issue; however, a conceptualization of dream self even reflects a more complicated process. Various historical and contemporary approaches, which need reconciliation and refinement, exist toward the topic of the self; these approaches spread through a wide spectrum. On the one hand is the thought that self is fictional; on the other hand, self is considered a solid concept. Of these approaches, the phenomenological approach has its own unique place capturing the issue from a broader view. While this phenomenological view argues that self is the subject of the self’s experiences, it also emphasizes the accessibility of self through consciousness. A descriptive introspection might access the basic phenomenal characteristics of the self. The present article basically argues that there is a phenomenal self in dreams that can be accessed through consciousness and thus, dreams are basically personal experiences of the self. Research into the phenomenological similarities and differences between the awake and dreaming self might help to better understand subjectivity and consciousness. On the other hand, if there exists a phenomenal self in dreams, which can be accessed through consciousness psychological dream theories need a radical revision.
Keywords: Consciousness; Dreaming; Self Theory of Dreams